2022
DOI: 10.1002/pssa.202100714
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Enriched Mesoporous Carbon Spheres as Efficient Anode Material for Long‐Cycle Li/Na‐Ion Batteries

Abstract: Nitrogen doping with carbon material substantially enhances the electrochemical properties in lithium and sodium batteries. However, direct treating at high temperature fails to create high nitrogen content, thus limiting the morphological as well as electrochemical performances. Herein, a hydrophilic material xanthan and acid‐treated melamine are doped by a dual process of hydrothermal and carbonization, enabling high nitrogen content (28%) carbon spheres. The highly defected nanosphere structures (ID/IG = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…These curves all have broad and dispersed diffraction peaks around 21.5° corresponding to the (002) reflection of graphite, again showing that the sample is amorphous carbon . In addition, it is found that the diffraction peaks corresponding to the graphite (100) reflection at about 44° are relatively weak for these three samples, which indicates the low crystallinity of these three materials . This may be caused by the introduction of template sodium chloride.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…These curves all have broad and dispersed diffraction peaks around 21.5° corresponding to the (002) reflection of graphite, again showing that the sample is amorphous carbon . In addition, it is found that the diffraction peaks corresponding to the graphite (100) reflection at about 44° are relatively weak for these three samples, which indicates the low crystallinity of these three materials . This may be caused by the introduction of template sodium chloride.…”
Section: Resultsmentioning
confidence: 87%
“…20 In addition, it is found that the diffraction peaks corresponding to the graphite (100) reflection at about 44°are relatively weak for these three samples, which indicates the low crystallinity of these three materials. 21 This may be caused by the introduction of template sodium chloride. According to the curve, the diffraction peak of CABP is more gentle than CA and CAB, suggesting that CABP has a more disordered carbon structure.…”
Section: Resultsmentioning
confidence: 99%
“…A key point to be illustrated is the great demand for anodes since graphite anodes exhibit scanty sites for Li + storage and poor cycle performance 11–13 . Compared with graphitized carbon, amorphous carbon doped with heterogeneous elements formed by high‐temperature pyrolysis generally display some unexpected properties: (1) Defects generated during pyrolysis can be regarded as active sites to store Li + 14–17 ; (2) Emerging greater layer spacing, which achieves rapid transmission of Li + and a high (de)lithiation rate 18–20 ; (3) Doped heterogeneous elements help to improve structural stability and ionic conductivity with additional Li + storage sites 21–23 …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Compared with graphitized carbon, amorphous carbon doped with heterogeneous elements formed by high-temperature pyrolysis generally display some unexpected properties: (1) Defects generated during pyrolysis can be regarded as active sites to store Li +14-17 ; (2) Emerging greater layer spacing, which achieves rapid transmission of Li + and a high (de) lithiation rate 18-20 ; (3) Doped heterogeneous elements help to improve structural stability and ionic conductivity with additional Li + storage sites. [21][22][23] Nitrogen doping of amorphous carbon is a representative strategy to fulfill high capacity, long life and an excellent rate carbonaceous anode. [24][25][26][27][28] Currently, template-assisted pyrolysis is usually used to synthesize 3D nitrogen-doped carbon (3D-NDC) anodes.…”
Section: Introductionmentioning
confidence: 99%
“…A key point to be illustrated is the great demand for anodes since graphite anodes exhibit scanty sites for Li + storage and poor cycle performance [11][12][13]. Compared with graphitized carbon, amorphous carbon doped with heterogeneous elements formed by high-temperature pyrolysis generally display some unexpected properties: (1) Defects generated during pyrolysis can be regarded as active sites to store Li + [14][15][16][17]; (2) Emerging greater layer spacing, which achieves rapid transmission of Li + and a high (de)lithiation rate [18][19][20]; (3) Doped heterogeneous elements help to improve structural stability and ionic conductivity with additional Li + storage sites [21][22][23].…”
Section: Introductionmentioning
confidence: 99%